Optimizing an enclosed bead beating extraction method for microbial and fish environmental DNA. Issue 2 (13th September 2021) - Anderson, Sean R.; Thompson, Luke R.
Abstract: DNA extraction is a critical step in processing environmental DNA (eDNA), influencing biodiversity estimates and ecosystem monitoring. Sterivex filters have become popular for collecting aquatic eDNA, allowing for on‐site filtration and reduced contamination. Yet, extracting eDNA from an enclosed filter remains laborious. Recent methods have improved extraction of microbial DNA from Sterivex by adding lysis buffer and beads directly to the filter; however, it remains unclear how bead size affects eDNA recovery across multiple trophic levels. Further, the method has not been scaled up for 96‐well magnetic bead extraction kits and robotic manipulation. We collected surface water from Bear Cut (Biscayne Bay, Florida) and performed enclosed Sterivex DNA extractions with different bead size combinations (0.1, 0.5, 0.1 + 0.5 mm, and no beads) and two magnetic kits (Zymo and NucleoMag). We employed 16S and 12S rRNA gene metabarcoding to assess extraction effects on microbes (bacteria, archaea, and eukaryotes) and bony fishes. We polled local experts to verify fish eDNA, revealing several non‐native taxa originating from a nearby aquarium. DNA yield, microbial richness, and diversity were not influenced by beads. Bacterial relative abundance (family to ASV) was conserved across bead treatments, while several hard‐to‐lyse eukaryotes (diatoms and chlorophytes) were less abundant (or absent) when extracted without beads. Higher fish richness was detected with larger beads; however, relative abundance and composition were not associated with beads, likely reflecting heterogeneity or low concentrations of fish compared to microbial eDNA. We recommend using larger or differently sized beads for Sterivex extractions to detect a range of marine life, with increased water volume (>2 L per filter) or replication as necessary to enhance fish eDNA capture. Abstract : Extraction is a critical step in processing environmental DNA (eDNA); however, best practices in aquatic eDNA extraction have yet to be resolved. We applied an enclosed Sterivex extraction protocol to test the effects of bead size and magnetic kit on the extraction of microbes and bony fishes. Our findings highlight important insights for Sterivex extraction across marine life, such as higher fish species richness with larger beads or the absence of key phytoplankton groups (diatoms) without beads, that will inform future aquatic eDNA research.